Obesity in adolescents may be associated with limitations in daily activities and an increased level of anxiety in patients and their parents – preliminary results of a pilot study - Wójcik, Małgorzata; Goncerz, Dawid; Piasny, Marta; Surówka, Anna; Mazurek, Edyta; Drożdż, Dorota; Kozioł-Kozakowska, Agnieszka; Starzyk, Jerzy B.; Makara-Studzińska, Marta (Frontiers in Endocrinology, 2022)
Obesity is a chronic disease, that in adolescents may lead to serious consequences affecting somatic and mental health. This study aimed to assess the prevalence of depressive symptoms and anxiety in adolescents with obesity and their parents. The relationships between depressive and anxiety symptoms and the somatic consequences of obesity were also analyzed. Material and Methods: 19 patients with obesity (BMI Z-SCORE 2.1-5.5), at the age 16-17, and their parents answered validated questionnaires (Children's Depression Inventory 2, The State-Trait Anxiety Inventory), and a survey assessing everyday functioning. Results: There were no significant differences in the occurrence of symptoms of depression in children and their parents: for the overall scale score of T-score (p=0.331), for the emotional problems (p=0.281) subscale, and the functional problems (p=0.147) subscale. The comparison of the results between boys and girls revealed no significant differences. A significantly higher level of anxiety was found in parents of children who gained weight in the year preceding the study (p = 0.046), and both in children and parents of children with metabolic-associated fatty liver disease – MAFLD (p=0.022 and p=0.007). According to adolescents, obesity affects the most leisure activities. Conclusion: Obesity, like any chronic disease, can have a significant impact on the emotional state of children and adolescents as well as the possibility of realizing interests and spending free time. Much more important than depressive disorders are anxiety disorders concerning both patients and their parents.